PENGARUH PEMANFAATAN TEKNOLOGI TERHADAP KEAMANAN LINGKUNGAN WISATA SITU CILODONG - Firman Syah; Tantri Sari Safitry; Karbala Madania (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
The purpose of this paper is to examine the use of technology for the security of the Situ Cilodong tourist environment. The local tourism potential in the area can encourage sustainable community participation. Using a mix of methods including field observations, group discussions with the community and the Tourism Awareness Group (Pokdarwis), and calculations using SPSS 25 related to the concept of tourism awareness and community-based destination development, the results show that Situ Cilodong is one of the natural tourism potentials in Depok City, which has attractions in the form of lakes and open spaces utilized by the community for recreation and social activities. However, this tourism potential has not been optimally maximized, both in terms of management, promotion, and community participation in the development of tourist destinations. During the FGD, problems arose with waste and security and order, so that information technology is needed that can be utilized in terms of tool use, benefits, and minimizing risks even through minimal training from the Pokdarwis. CCTV was chosen to monitor the movement of the entire area while maintaining the comfort of local residents and tourists in a sustainable manner.